THE HISTORY OF THE TRADITIONAL JONGGAN DANCE IN THE DAYAK KANAYATN COMMUNITY OF WEST KALIMANTAN PROVINCE FROM 1998 - 2025: Sejarah Tarian Tradisional Jonggan dalam Masyarakat Suku Dayak Kanayatn Provinsi Kalimantan Barat pada Tahun 1998-2025 - Priyanto Widodo; Aulia Fitriany; nichodemus Nichodemus (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research discusses the history of Jonggan traditional dance in the Dayak Kanayatn community, West Kalimantan, from 1998 to 2025. The research objectives include understanding the dynamics, socio-cultural roles, and relevance of Jonggan dance to education in that time span. The research uses historical method with four stages: source collection (heuristics), source criticism (verification), interpretation, and writing (historiography). The results showed that Jonggan dance experienced significant changes due to technological advances and the influence of foreign cultures. Its popularity has decreased because the younger generation is less concerned about preserving it, causing a decrease in value in society. The meaning of the dance also shifted from sacred rituals and cultural identity to commercial performances that lost symbolic and spiritual contexts. Sacred elements, such as social satire verses are now diminishing due to excessive commercialization. The change in values occurred because indigenous people began to adjust to modern entertainment, such as local bands and DJs that are more attractive to the younger generation. As a result, Jonggan dance is considered boring and has lost its appeal. The regeneration crisis of Jonggan dance is getting worse due to the lack of support from the government and educational institutions. This shows that without serious preservation efforts, traditional dances such as Jonggan can become extinct and lose their place in the socio-cultural life of the Dayak Kanayatn community.